Interior Design of Daycare Center with Playful Concept in Salatiga - Habiba Intan; IF. Bambang Sulistyono (Institut Seni Indonesia Surakarta, 2021)
Along with the rise in career women, the community is seeing an increase in daycare centers to prevent child abuse and provide early childhood education. Language skills, character development, creativity, and motor skills are all part of this education. However, most daycares, particularly those for youngsters, place less emphasis on amenities and infrastructure. Many daycares have not followed the rules. As a result, a concept arose for a Daycare Center with a Playful Concept in the City of Salatiga, complete with an infant room, playground, classroom, sleeping room, canteen, and Office.